The Role of Targeted Focal Therapy in the Management of Low-Risk Prostate Cancer: Update on Current Challenges. (31st December 2012) - Smith, Daniel W.; Stoimenova, Diliana; Eid, Khadijah; Barqawi, Al
Abstract : Prostate cancer is one of the most prevalent cancers among men in the United States, second only to nonmelanomatous skin cancer. Since prostate-specific antigen (PSA) testing came into widespread use in the late 1980s, there has been a sharp increase in annual prostate cancer incidence. Cancer-specific mortality, though, is relatively low. The majority of these cancers will not progress to mortal disease, yet most men who are diagnosed opt for treatment as opposed to observation or active surveillance (AS). These men are thus burdened with the morbidities associated with aggressive treatments, commonly incontinence and erectile dysfunction, without receiving a mortality benefit. It is therefore necessary to both continue investigating outcomes associated with AS and to develop less invasive techniques for those who desire treatment but without the significant potential for quality-of-life side effects seen with aggressive modalities. The goals of this paper are to discuss the problems of overdiagnosis and overtreatment since the advent of PSA screening as well as the potential for targeted focal therapy (TFT) to bridge the gap between AS and definitive therapies. Furthermore, patient selection criteria for TFT, costs, side effects, and brachytherapy template-guided three-dimensional mapping biopsies (3DMB) for tumor localization will also be explored.